Looking back to look forward: a systematic review of and research agenda for dynamic managerial capabilities - Tim Heubeck (Management Review Quarterly, 2023)
Given the complexities of today's hypercompetitive economy and challenges imposed by recent crises, managerial capabilities have become critical for realizing strategic change. Dynamic managerial capability (DMC) theory offers a useful theoretical lens for analyzing how managers make strategic decisions to build and sustain competitive advantages in dynamic environments. Despite receiving less attention than the broader field of dynamic capabilities, the existing body of research has reached a point where a comprehensive synthesis of the current state of knowledge is warranted. Past reviews of DMCs are either outdated or do not comprehensively examine this multifaceted construct, making a review of research highly necessary and timely. This review systematically synthesizes 54 empirical studies on DMCs. It contributes to the literature by systematically synthesizing DMC research and summarizing these findings into a multi-level framework. This review demonstrates that research on DMCs has significantly progressed over the years, for example, through conceptual expansions, new levels of analysis, or methodological advancements. The developed framework provides an overview of the nomological network surrounding DMCs. A systematic historical analysis of research limitations and recommendations offers a rich research agenda for DMCs. These findings guide scholars and managers by overviewing the foundations of DMCs, demonstrating why strong DMCs are critical for achieving sustainable competitive advantage, and how this theory applies to management practice. Altogether, this review presents an up-to-date review of DMC literature by systematically synthesizing its developments— looking back —and pointing to central research opportunities— looking forward .
Keywords: M10; M12; 650; Dynamic managerial capabilities; Human capital; Managerial cognition; Social capital; Systematic literature review